Efficacy and Safety of Oral Chinese Herbal Medicine for Migraine: A Systematic Review and Meta-Analyses Using Robust Variance Estimation Model - Lyu, Shaohua; Zhang, Claire Shuiqing; Guo, Xinfeng; Zhang, Anthony Lin; Sun, Jingbo; Chen, Genghang; Xue, Charlie Changli; Luo, Xiaodong (Frontiers in Neurology, 2022)
Background Migraine is a prevalent headache disorder with significant impacts on patients' quality of life and economic burden. Chinese herbal medicine (CHM) is commonly prescribed for migraine in China. This review aimed to provide a rigorous evaluation of evidence on the efficacy of oral CHM for migraine and explore the correlation between its effect size and treatment duration. Methods We searched nine digital databases (PubMed, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, AMED, BioMedical Literature, CNKI, CQVIP, and Wanfang Data) from their inceptions to May 2021, with the language being restricted to Chinese and English. Randomized, placebo-controlled trials using oral CHM to treat adult migraine were included. Data screening and extraction were conducted by two independent reviewers. The methodological quality of randomized controlled trials (RCTs) was assessed using the Cochrane Risk of Bias tool. Meta-analyses were conducted to estimate the effect size using a random effect model, and a robust variance estimation (RVE) model was constructed to explore the correlation between treatment effects and treatment duration. The certainty of the evidence was assessed with the Grading of Recommendations Assessment, Development, and Evaluation. Publication bias was tested using a funnel plot and Egger's test. Results A total of 18 RCTs involving 3,015 participants were included. Results of the meta-analyses showed that, at the end of the treatment phase, CHM was more efficacious than placebo in reducing migraine frequency, migraine days, and pain severity, and increasing response rate. Additionally, CHM showed superior effects to placebo in lowering migraine frequency and pain severity at the end of the 4-week follow-up. The RVE model suggested that the benefits of CHM for migraine frequency and pain intensity increased as treatment duration extended. The number of adverse events reported by the CHM and placebo groups was comparable. The certainty of the evidence was graded as “moderate.” No publication bias was detected. Conclusion Oral CHM appeared to be more efficacious than placebo for reducing migraine frequency and pain severity. Greater treatment effects were associated with longer treatment duration. The oral CHM was well tolerated. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#recordDetails, identifier: CRD42021270719.